Case Report: Clinical awareness about the effect of laser interstitial thermal therapy on pediatric high-grade brain tumors after radiotherapy - Fernandes Dias, Sandra; Oertel, Markus F.; Guerreiro Stücklin, Ana; Gerber, Nicolas U.; Colombo, Elisa; van Doormaal, Tristan P. C.; Krayenbühl, Niklaus (Frontiers in Surgery, 2025)
The use of magnetic resonance-guided laser interstitial thermal therapy (LITT) for the treatment of brain tumors and epileptic lesions has increased in the field of pediatric neurosurgery. However, very little is known about the effect of LITT on pediatric high-grade tumors that have been previously treated with radiotherapy. We report on two cases of children with an unexpected rapid brain tumor progression after LITT. The first case was an 11-year-old boy with a periventricular metastasis of a recurrent anaplastic ependymoma treated with proton-therapy and radiosurgery. The second case was a 6-year-old girl with a Lynch-syndrome and a recurrence of a mesio-temporo-occipital high-grade glioma admitted to gross total resection, proton-therapy, chemotherapy, bevacizumab and immune checkpoint inhibitor. Due to evidence of tumor progression in both cases, a decision was made to perform LITT. Shortly after the laser ablation, we observed a significant tumor growth along the trajectory of the LITT catheters, accompanied by clinical deterioration. The effect of LITT on pediatric ependymoma and high-grade glioma recurrence after radiotherapy is still unclear. The tumor expansion following LITT in these two patients should drive a deeper awareness of the effect of radiation and LITT on the tumor-environment. The breakage of the morphogenetic boundaries of the neuromeres, to which each tumor was initially confined, through the placement of the LITT catheters should be considered while trying to understand the disease spread mechanisms. Based on the experience of our center, we advise a careful implementation of this technique on pediatric high-grade central nervous system tumors, particularly in recurrent tumors that were previously treated with radiotherapy, until the underlying pathophysiologic mechanism has been better understood.